Efektifitas Dents-Voice untuk Meningkatkan Pengetahuan Kesehatan Gigi dan Mulut serta Penurunan Debris Indeks - Yeni Maryani; Rita Herlina; M. Ibraar Ayatullah (JURNAL INFO KESEHATAN, 2019)
60.5% of the population in West Kalimantan have problems with oral health. One of them is children with special needs who are blind. Promoting media used for children with special needs is different from the media used for healthy children. Dents-Voice is a teaching aid designed for children with visual impairment as a media for counseling oral health. This device will make a sound when the button is pressed. The sound that comes out is in the form of information relating to damage to the teeth, causes and how to prevent them. This study aims to discover the effectiveness of Dents-Voice props as an educational medium in improving dental and oral health knowledge and can reduce the index debris of the blind. This research is a quasi-experimental pre and posttest without control from a quantitative approach. This research was conducted at SLBN Mempawah Hilir, Ar-Rahmah Foundation, and Al-Iqra Foundation. The population of this research was 21 people. The sample of this study used a total sampling technique. The results of the study used a Paired Sample T-Test; the average value of respondents' initial knowledge was 71.86 and after counseling it, it rose to 90.71 with a P.Value of 0,000. The average value of the respondents' initial index debris was 1.80 and after counseling it, it dropped to 1.09 with a P.Value value of 0,000. The conclusions of this study show that Dents-Voice is effective for increasing knowledge and decreasing the debris index for the blind.